VALUE CHAIN ANALYSIS IN INDOMARET RAWA SIMPRUG KEBAYORAN LAMA - Sri Mulyono; Shintia Nuraprila; Hanifa Hana Kamila; Nadira Awalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The value chain is a tool for analyzing competitive advantages and creating the right technology to enhance those advantages. In this article, the value chain is used to analyze the small retail market industry. Retail is the end point of all activities in the distribution channel that connects producers and consumers to sell a product or Service. The retail store used for the analysis is Indomaret Rawa Simprug which is located in Kebayoran Lama. The research method used is descriptive, using raw data obtained through field observations, interviews and recording. The results of the analysis obtained to increase competitive advantage is to increase product variety because it will make it easier for customers to find what they are looking for. Beyond that, the focus is on maximizing the existing community by meeting their every need. What needs to be maintained and improved is to expand the dealer network because with the increase in the number of dealers, products will get cheaper prices and will change the selling price of products, store appearance, use of technology, detailed SOPs and customer Service.